2009
DOI: 10.1007/s11200-009-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Continuous gas monitoring in the West Bohemian earthquake area, Czech Republic: First results

Abstract: Two stations monitoring concentrations of carbon dioxide and radon in soil gas (Oldřišská and Nový Kostel) and one station monitoring flow of carbon dioxide at a mofette (Soos) have been operated in the area of the West Bohemian earthquake swarms. We present preliminary results obtained on the base of four-year observations. We found that data are not influenced considerably by barometric pressure. Although the CO 2 concentration varies greatly, the long-term trends at stations Oldřišská and Nový Kostel are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…As an example, observations of CO 2 gas emanation (e.g. Faber et al, 2009), gravimetric measurements (Mrlina and Seidl, 2008;Kämpf, et al, 2008), GPS measurements (Schenk et al, 2009), micro-network observation (Häge and Joswig, 2008). We made an attempt to record the electromagnetic emission (here after EME) excited by seismic activity.…”
Section: West Bohemia Earthquake Regionmentioning
confidence: 99%
“…As an example, observations of CO 2 gas emanation (e.g. Faber et al, 2009), gravimetric measurements (Mrlina and Seidl, 2008;Kämpf, et al, 2008), GPS measurements (Schenk et al, 2009), micro-network observation (Häge and Joswig, 2008). We made an attempt to record the electromagnetic emission (here after EME) excited by seismic activity.…”
Section: West Bohemia Earthquake Regionmentioning
confidence: 99%
“…The swarm was located in the southern part of the main Nový Kostel focal zone, where the fault plane is striking 168°N and dipping 80° westward, Figure [ Fischer and Horálek , ]. Previous studies suggested a connection between the common occurrence of deep‐seated fluids (mostly mantle‐derived CO 2 ‐rich fluids) and seismicity, where the observed anomalies may reflect a seismically induced release of fluids and/or changes in fluid migration pathways [ Bachura and Fischer , ; Bräuer et al, ; Bräuer et al, ; Faber et al, ; Horálek and Fischer , ; Koch et al, ; Koch and Heinicke , ; Kämpf et al, ].…”
Section: Field Site and Methodsmentioning
confidence: 99%
“…). Secular variations of environmental tracer concentrations in groundwater, such as 3 H, 85 Kr and SF 6 are used for groundwater dating. Spontaneous changes have been reported and related to seismic activity …”
Section: What Can Be Learned From Natural and Technical Analogs?mentioning
confidence: 99%